Service Recovery on Customer Repurchase Interest with Service Quality as a Mediation on FnB Consumers - Kurniawati, Devi Yulia; Fajri, Annisa (Economics and Business International Conference Proceeding, 2024)
This type of research is classified as descriptive research. The population of this research is all FnB custumers in Semarang. Determining the sample size in this study used the Chocran formula with a sample size of 97 respondents with a sampling technique using the purposive sampling method. The sampling technique uses a questionnaire while secondary data is in the form of documentation. For data analysis using the SmartPLS 3 program. The results of this research show 1). Service Recovery has a significant positive effect on the Repurchase Intention of FnB customers in Semarang, 2) Service Recovery has a positive and significant effect on the Service Quality of FnB Custumers in Semarang, 3) Service Quality has a positive and significant effect on the Repurchase Intention of FnB Custumers in Semarang, 4) Service Quality has a positive and significant effect on Repurchase Intention through Service Recovery.